Replantation as treatment for extrusive luxation - Hamanaka, Elizane Ferreira [UNESP]; Nogueira, Lamis Meorin [UNESP]; Pires, Willian Ricardo [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP]; Sonoda, Celso Koogi [UNESP] (Fundação Odontológica de Ribeirão Preto, 2015)
In the treatment of extrusive luxation cases, it is important that the repositioning of extruded tooth in the socket is done as soon as possible. If this does not occur, periapical clot becomes organized and makes replantation difficult reposition. In this article the patient referred to the Clinics for dental trauma sustaining extrusive luxation of the maxillary right central incisor. The patient reported having suffered a bicycle accident 12 days before, which caused traumatic tooth injuries. The repositioning was attempted without success and an alternative form of treatment was necessary to solve the case. Intentional tooth replantation, which is the deliberate extraction of the tooth and its replantation, was indicated. This technique allows clot removal and correct repositioning of the extruded tooth. Care should be taken as endodontic treatment is required for the prevention of subsequent infection-related resorption. Intracanal dressing with calcium hydroxide was used for 30 days before final root filling. Splint, systemic antibiotics and avoidance of further damage to the root surface is also important. After 49 months, showed clinical and radiographic characteristics of normality and demonstrates the availability of this technique to adversity in trauma.

No tratamento de casos de luxação extrusiva é importante que o reposicionamento do dente extruído em seu alvéolo seja feito o mais rápido possível. Se isso não ocorrer, o coágulo periapical se torna organizado e dificulta a reposição. Neste artigo, o paciente encaminhado para a clínica de traumatismo dentário apresentava luxação extrusiva do dente 11. O paciente relatou que havia sofrido um acidente de bicicleta 12 dias antes e teve lesões dentárias. Tentou-se fazer o reposicionamento sem sucesso e uma forma alternativa de tratamento foi necessária para resolver o caso. Reimplante intencional, que é a extração do dente e seu reimplante de forma proposital, foi indicado. Esta técnica permite a remoção do coágulo e o reposicionamento correto do dente extruído. Cuidado deve ser observado quanto ao tratamento endodôntico, para a prevenção de uma reabsorção relacionada a uma infecção. Curativo de demora com hidróxido de cálcio foi realizado por 30 dias antes da obturação final. Contenção, antibióticos sistêmicos e evitar maiores danos à superfície da raiz também são importantes. O controle de 38 meses mostrou características clínicas e radiográficas de normalidade e demonstra a disponibilidade desta técnica para a adversidade no trauma.
Keywords: intentional replantation; extrusive luxation; calcium hydroxide